2015
DOI: 10.1111/aor.12488
|View full text |Cite
|
Sign up to set email alerts
|

A Diagonal‐Steering‐Based Binaural Beamforming Algorithm Incorporating a Diagonal Speech Localizer for Persons With Bilateral Hearing Impairment

Abstract: Previously suggested diagonal-steering algorithms for binaural hearing support devices have commonly assumed that the direction of the speech signal is known in advance, which is not always the case in many real circumstances. In this study, a new diagonal-steering-based binaural speech localization (BSL) algorithm is proposed, and the performances of the BSL algorithm and the binaural beamforming algorithm, which integrates the BSL and diagonal-steering algorithms, were evaluated using actual speech-in-noise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Jun Chang Lee et al of Hanyang University, Seoul, Korea reported a new diagonal‐steering‐based binaural speech localization (BSL) algorithm. Testing sounds were recorded in a KEMAR mannequin setup and two objective indices, improvements in signal‐to‐noise ratio (SNRi) and segmental SNR (segSNRi), were utilized for performance evaluation.…”
Section: Auditory Supportmentioning
confidence: 99%
“…Jun Chang Lee et al of Hanyang University, Seoul, Korea reported a new diagonal‐steering‐based binaural speech localization (BSL) algorithm. Testing sounds were recorded in a KEMAR mannequin setup and two objective indices, improvements in signal‐to‐noise ratio (SNRi) and segmental SNR (segSNRi), were utilized for performance evaluation.…”
Section: Auditory Supportmentioning
confidence: 99%